Activity of the kynurenine pathway and its interplay with immunity in patients with pulmonary arterial hypertension. Issue 3 (14th January 2016) - Jasiewicz, Malgorzata; Moniuszko, Marcin; Pawlak, Dariusz; Knapp, Malgorzata; Rusak, Malgorzata; Kazimierczyk, Remigiusz; Musial, Wlodzimierz Jerzy; Dabrowska, Milena; Kaminski, Karol Adam
Abstract : Objective: We evaluated blood concentrations of kynurenine pathway metabolites, natural and induced regulatory T cells (nTreg, iTreg), and Th17 cells in order to examine the activity of the kynurenine pathway and its relation to immune status in patients with pulmonary arterial hypertension (PAH). Methods: Plasma concentrations of tryptophan, kynurenine, kynurenic acid, anthranilic acid, and 3-hydroxykynurenine were quantified in 26 patients with PAH (vs 30 healthy controls) at baseline and after 6 months, and assessed them in relation to clinical parameters, frequencies of lymphocyte subsets, and outcome. Results: The PAH group presented higher concentrations of tryptophan (52.9 (IQR 46.3–57.5) vs 40.3 (35.2–46.3) µmol/L, p=0.00003), kynurenine 2.8 (2.4−3.4) vs 1.9 (1.5–2.3) µmol/L, p=0.000007), kynurenine/tryptophan ratio (0.051 (0.044–0.064) vs 0.043 (0.039–0.055), p=0.03), iTreg frequencies (10.5 (8.8–13.9)% vs 6.8 (5.2–9.5)%, p=0.002) and iTreg/Th17 (1.73 (1.2–2.8) vs 0.93 (0.61–1.27), p=0.003) together with lower ratios of kynurenic acid/kynurenine, 3-hydroxykynurenine/kynurenine, and anthranilic acid/kynurenine. Kynurenine concentrations and kynurenine/tryptophan ratio correlated positively with iTreg/Th17, and inversely with Th17 subsets, whereas kynurenic acid/kynurenine and anthranilic acid/kynurenine ratios correlated positively with Th17. Adverse outcomes occurred in 9 of 26 patients and they showed higher baseline concentrations of kynurenine (3.6 (2.8–4.3) vs 2.7 (2.1–3.2) µmol/L, p=0.033). Median kynurenine values ≥3.4 µmol/L (67% sensitivity, 94% specificity) identified patients with a worse clinical course. Conclusions: PAH is characterised by upregulated tryptophan metabolism and enhanced biosynthesis of kynurenine. Elevated kynurenine concentration is associated with an adverse clinical course. Dysregulated immunity, delineated by Treg-Th17 imbalance, is directly related to diverse activation of the kynurenine pathway, indicating the potential interplay between kynurenines and the immune system in PAH.